Energy minimization methods in computer vision and pattern recognition: 10th international conference, EMMCVPR 2015, Hong Kong, China, January 13 - 16, 2015 ; proceedings - Tai, Xue-Cheng (Lecture notes in computer science, 2015)
Discrete and continuous optimization -- Image restoration and inpainting -- Segmentation -- PDE and variational methods -- Motion, tracking and multiview reconstruction -- Statistical methods and learning -- Medical image analysis.